The keepsake : a novel - Gerritsen, Tess. (New York : Ballantine Books, 2008)
Dr. Maura Isles is intrigued by an offer to observe the X- raying of a mummy -- until she discoves that the mummy is a contemporary murder victim.
Keywords: Rizzoli, Jane, Detective (Fictitious character) -- Fiction; Policewomen -- Fiction; Women -- Crimes against -- Fiction; Medical examiners (Law) -- Fiction; Women forensic scientists -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction